5: QUANTITATIVE ANALYSIS OF DESMOPRESSIN (DDAVP) RESPONSE IN ADULT PATIENTS WITH TYPE 1 VON WILLEBRAND DISEASE. Issue 3 (March 2016) - Guddati, AK
Abstract : Purpose of Study: Patients with Type I vWD have reduced amounts of Willebrand Factor (vWF) in their blood. Desmopressin (DDAVP) has been used to raise the serum levels of vWF in these patients. However, not all patients with Type 1 vWD are known to respond to DDAVP therapy. We sought to compare the levels Factor VIII, vWF antigen, ristocetin and fibrinogen at different time points to determine the single most useful time point for ascertaining the patient as a responder. Methods Used: Levels of Factor VIII, vWF antigen, ristocetin and fibrinogen has been conventionally measured at multiple time points after a DDAVP challenge. We conducted a retrospective analysis on 89 patients who received the DDAVP challenge test and compared their factor levels at 0, 30, 60, 90 and 120 minutes. Summary of Results: Levels of Factor VIII, vWF antigen ristocetin and fibrinogen were significantly elevated (p<0.001) at 30, 60, 90 and 120 minute time points when compared to their baseline values. A downtrend was noted for Factor VII, vWF antigen and ristocetin levels at the 90 minute time point but fibrinogen levels did not significantly change compared to the baseline level. Conclusions: In this study we show that measurement of factor levels at any one time point, preferably at 60 minutes is sufficient to diagnose a patient as a responder after a DDAVP challenge test. Curtailing the number of time points of measurement will result in significant savings in cost and time to patients and their providers.